2022
DOI: 10.1108/cdi-06-2020-0156
|View full text |Cite
|
Sign up to set email alerts
|

Torn between individual aspirations and the family legacy – individual career development in family firms

Abstract: PurposeThe purpose of this paper is to explore individual career management by family members in the context of their family firms.Design/methodology/approachThe interpretative interview study of family members active in family businesses explores how this context affects the choice, planning, goals and development of family members' careers in their family business.FindingsThe authors find that career management in the family business setting focuses on fulfilling the family business goals rather than the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
4
0
2
Order By: Relevance
“…It can either improve or impede the firm's performance (Gabriel and Bitsch, 2018; Molly et al ., 2010). Family businesses often prioritize long-term sustainability, noneconomic goals and the preservation of family values and reputation, known as SEW (Achtenhagen et al ., 2022; Hammond et al ., 2016). Intergenerational succession is a crucial step in ensuring the business's continuity and success across generations (Fendri and Nguyen, 2019; Porfírio et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can either improve or impede the firm's performance (Gabriel and Bitsch, 2018; Molly et al ., 2010). Family businesses often prioritize long-term sustainability, noneconomic goals and the preservation of family values and reputation, known as SEW (Achtenhagen et al ., 2022; Hammond et al ., 2016). Intergenerational succession is a crucial step in ensuring the business's continuity and success across generations (Fendri and Nguyen, 2019; Porfírio et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies show that successors tried to avoid the increase in borrowing, following taking over the control of the firm (Kaye and Hamilton, 2004), while other studies showed successors may increase debts to finance the firm's growth (Bjuggren and Sund, 2005). Moreover, business owners who consider intergenerational succession may have the desire to build up a family legacy (Achtenhagen et al ., 2022; Hammond et al ., 2016; Kalali, 2022) and adopt a long-term orientation, which is likely to inhibit firm financialisaton—a phenomenon that is characterised by short-termism, down-sizing and reduced innovativeness (Buchanan, 2017; Demir, 2009; Hahn, 2019; Lazonick and O'sullivan, 2000). Nevertheless, there has not been any empirical test of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies insist on its benefits for shaping family legacy (e.g., Combs et al, 2023; Lorandini, 2015; Pérez & Puig, 2004) and entrepreneurial legacy alike (e.g., Buckman et al, 2019; Roscoe et al, 2013; Tarling et al, 2016). Conversely, Achtenhagen et al (2022) demonstrate that strategic education can also be a “trap” when the needs of the family firm guide educational processes and goals, with little respect or attention to the needs of those expected to accept family legacy. Working within the family business might thus become a “default option” rather than a vocational or passion-based choice (p. 212).…”
Section: How Is Legacy Sent and Received?mentioning
confidence: 99%
“…Sometimes, family legacy becomes negative. For instance, drawing on career management theory, Achtenhagen et al (2022) reveal family legacy as a source of constraint for the next generation when the legacy built by the senior generation aims at satisfying the business expectations of legacy senders relative to succession without respecting the dreams and hopes of the offspring.…”
Section: Who Sends and Receives Legacy?mentioning
confidence: 99%
“…Empresas familiares são negócios administrados por uma ou mais famílias com a intenção de seguir a visão e os valores mantidos por membros da família, ao longo das gerações (Chua et al, 1999). São organizações em que a gestão de carreira dos membros da família tende a ser vinculada à empresa familiar (Achtenhagen et al, 2022). Em meio à influência da coalizão dominante que há no ambiente dessas empresas (Chua et al, 1999), os colaboradores desenvolvem identidades familiares e organizacionais, relacionadas com os valores constituídos pelos membros da família (Carmon & Pearson, 2013).…”
Section: Referencial Teóricounclassified